Comparative Analysis Of Community-Based Ecotourism In Four Serdang Bedagai Villages In Integrating Educational Innovations In Conservation Forest Management - Faried, Annisa; Sembiring, Rahmad; Rahayu, Sri; Novita Sari Manik, Rika; Abdelhakeem Khalid Ahmed, Azam (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This research investigates forest management practices in conservation zones implementing community-based ecotourism approaches across four distinct coastal regions in North Sumatra: Kota Pari, Pantai Cermin, Perbaungan, and Teluk Mengkudu Villages. By examining these locations, we sought to provide a comparative assessment of education-centered management frameworks and their effectiveness in ecological preservation and community development within varying socioeconomic environments. Method: Our methodology incorporated field observations, stakeholder interviews with 60 key informants, document analysis, mixed-method data evaluation, and 8 focus group discussions conducted throughout January-December 2023. We surveyed 400 households (100 per village) to gather quantitative data regarding educational impacts, conservation perceptions, knowledge acquisition, and CBE program participation levels. Data analysis employed comparative thematic methodology and triangulation from multiple sources to enhance finding validity. Results: Findings revealed notable differences in educational approaches to community-based ecotourism among the researched locations. Kota Pari demonstrated superior results with a 71% reduction in illegal logging and development of 24 knowledge-based livelihood activities. Pantai Cermin successfully leveraged tourism dynamics for environmental education through visitor-community learning exchanges, while Perbaungan Village effectively addressed agricultural-conservation tensions through structured intergenerational knowledge transfer. Teluk Mengkudu Village, having adopted this model most recently (two years prior), showed promising results through its youth-centered educational approach despite resource limitations. Cross-village analysis revealed that implementation duration, educational approach quality, institutional support, and community socioeconomic characteristics significantly influenced program outcomes. Novelty: This study contributes three novel insights to the field: (1) it identifies developmental pathways for educational components in community-based conservation, demonstrating how approaches evolve from targeted activities in early implementation toward comprehensive learning systems as programs mature; (2) it positions education not merely as information transfer but as a transformative process developing community capabilities for both environmental stewardship and sustainable livelihoods; and (3) it challenges conventional distinctions between conservation education and economic development by demonstrating how integrated approaches can simultaneously build ecological knowledge, practical skills, and entrepreneurial capacities. The research provides evidence-based recommendations for designing adaptable education-centered Community Based Ecotourism models applicable across diverse socioeconomic contexts and implementation phases.